Egalitarian envy: Cross-cultural variation in the development of envy in children - Kirsten Häger; Bastian Oud; Daniel Schunk (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
While envy has been studied extensively in adults, the question how envy develops during childhood has not received much attention. To address this gap, we report the results of an artefactual field experiment that investigates and compares the prevalence and development of destructive envy in children aged seven to ten. The experiment took place in the childrens natural environment - their schools. We also checked for cultural variability of our results by conducting our study with German children and with children from a highly egalitarian society: the Eastern Penan of northern Borneo. We found that envious behavior was prevalent already at a young age, even when it was costly. An egalitarian upbringing did not appear to mitigate this prevalence. Furthermore, we found strong evidence of cultural variability in the development of envy in children. For instance, in contrast with the German sample, gender was not associated with envy in the Penan sample and the age pattern of envy differed across our two groups. Together, this suggests that there does not appear to be a straightforward relationship between the development of envy and the natural development of the human mind with age, e.g. through better mentalizing ability. Rather, the acquisition pattern of envy is modulated by socio-cultural context. Further research is needed to identify what, then, drives the development of envy during childhood.
Keywords: C91; C99; 330; artefactual field experiment; children; envy; egalitarianism; Germany; Penan; Malaysia; Neid; Kinder; Feldforschung; Deutschland; Malaysia